The Impact of Proactive Personality and Individual Cybersecurity on Technostress: A Study on Aviation Sector Employees (Third Sector Social Economic Review, 2026)
This study aims to examine the relationships between proactive personality traits and individual cybersecurity behaviors and technostress levels, as well as their predictive roles, among employees in the aviation sector. In today’s rapidly digitalizing work environments, employees’ responses to technology-related stressors have become increasingly important. Within this context, the study investigates whether individual-level personality traits and cybersecurity behaviors are significantly associated with technostress. The research was conducted using a quantitative method, and data were collected through a questionnaire from 387 employees working in the aviation sector in Türkiye. The data were analyzed using correlation analysis, independent samples t-test, group comparison tests, and multiple linear regression analysis. The findings indicate that proactive personality is negatively associated with technostress, whereas individual cybersecurity behaviors are positively associated with technostress; both variables are significant predictors of technostress. In addition, comparisons based on demographic variables revealed significant differences in some research variables according to gender, marital status, occupational status, age, education level, and tenure. The results suggest that organizations seeking to enhance employee well-being may benefit from developing practices that support proactive personality traits and integrating cybersecurity training with stress management.
Keywords: Proactive Personality; Technostress; Individual Cybersecurity; Aviation Sector; Organizational Behavior